Relationship between macroeconomic variables towards stock prices from year 2004-2009/ Ungku Nur Hasyirah U. Iskandar - U. Iskandar, Ungku Nur Hasyirah (Faculty of Business and Management, 2011)
This paper aims to investigate the dynamic interaction between four macroeconomic variables and the stock prices from year 2004 until 2009. The macro variable consists of Gross Domestic Product, Consumer Price Index, Interest Rate on Treasury Bills and Exchange Rate of Ringgit Malaysia against US Dollar. The cointegration and causality Error Correction Model (ECM) were used in this study, to analyze the disequilibrium in the short-run and long-run relationship among the variables thus determine the stability and normality of data series. By using Johansen’s Cointegration Test, this study concludes that there is long run relationship exists between stock prices and explanatory variables with lag order of 2. There is also uni-directional causality existed between GDP and stock prices and interest rate with stock prices. After applying Lagrange-Multiplier Test and Jarque Bera Test, the result indicates that there is no autocorrelation problem existed and the data series is normally distributed. Finally, both positive and negative direction shown in this research where GDP and Exchange Rate were found to be in positive relationship with stock prices while CPI and Interest Rate show a negative relationship occur between them.